ISLAMIC BOARDING SCHOOL AND CHARACTER EDUCATION AT KHALAF ISLAMIC BOARDING SCHOOL (RESEARCH AT THE BAITUL MUSLIM ISLAMIC BOARDING SCHOOL, LABUHAN RATU SATU VILLAGE, WAY JEPARA DISTRICT, EAST LAMPUNG REGENCY, LAMPUNG PROVINCE) - Amet, Amet (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research on the Khalaf Islamic Boarding School and Character Education was carried out using a qualitative approach. Data collection in this research was carried out through interviews, documentation and observation. Islamic boarding schools with various types and models that have developed in all corners of the country are the biggest contributor to the maintenance of the values of the nation's character, where up to now there are still very few events that indicate the uprooting of the nation's noble values in social, national and state life. . The results of the research show that the Baitul Muslim Way Jepara East Lampung Islamic Boarding School is one of the Khalaf Islamic Boarding Schools which is an alternative choice as an Islamic Education Institution that is able to adapt to various advances and developments in modern science and is integrated with moral/character education launched by the Indonesian government as a means of learning, instilling, internalizing the nation's noble values, and forming the character of students at all levels of educational units are the central points of national education development through the Pancasila Student Profile Strengthening Project